Lyman Continuum Leakers at z > 3 in the GOODS-S Field: Mergers Dominated - Shuairu Zhu; Zhen-Ya Zheng; Fang-Ting Yuan; Chunyan Jiang; Ruqiu Lin (The Astrophysical Journal Letters)
Understanding the ionizing photon escape from galaxies is essential for studying cosmic reionization. With a sample of 23 Lyman continuum (LyC) leakers (among which eight are high-confidence leakers) at 3 <  z  < 4.5 in the GOODS-S field, we investigate their morphologies using high-resolution data from the Hubble Space Telescope and the James Webb Space Telescope. We find that 20 of the 23 LyC leakers (seven out of eight high-confidence leakers) show merging signatures via visual inspection, while the remaining three are starbursts. The merger fraction of our sample is significantly higher than that of normal galaxies at similar or higher redshifts. Even when using the nonparametric method, which may miss some mergers in a sample, the merger fraction remains high, especially for the high-confidence leakers. Based on our previous finding that LyC leakers are not necessarily starbursts while some are in the star formation main sequence, we further find that those in the main sequence show merger signatures. Our results suggest that LyC leakers are either starbursts or mergers, both of which can facilitate the LyC photon escape, in addition to generating more LyC photons. Furthermore, we show that high- z LyC leakers are statistically more extended than those selected at low redshift, which exhibit a higher merger fraction as size increases. This is likely due to the observational bias that the spatial resolution limits the detection of high- z compact galaxies, while low redshift LyC leakers are more selected as compact starbursts.